(untitled) (Medico Legal Update, 2021)
Background: The spread of antimicrobial-resistance had continuously emerged among S. aureus strains poses a major concern in treating the infection with this bacterium and established a challenge to clinical laboratories. Consequently, measuring resistance is essential to provide a clinical service for patients with S. aureus infections. Methods: S. aureus was isolated from burn and wound injuries and identified according to the biochemical tests, then genotyped through Spa-typing method to diagnose at the strain level.The antibiotic resistance patterns of the 18 S. aureus strains were studied by Kirby-Bauer assay and the inhibition zone was measured. Results: The antibiotic results of each spa-type were discussed according to the globally published researches. Moreover, the spa-type of this study was grouped into two groups, one with high resistance and the other with less resistance. Conclusion: In conclusion, the high resistance bacterial group infects injuries that needed a long period to be healed, and the refore it is recommended to have a strict sterilized separated environment for cases most prone to infections such as patients with a burn or diabetic foot injuries.